Design and Development of Pharmacosome Loaded with Piroxicam to Improve Oral Bioavailability: Pharmaceutical Science-Pharmaceutics - S, Muthukumar; C, Sankar; R, Gayathri; R, Manoranjan; A, Mohandass; B, Rajaguru; V, Rajeshwari; P.v, Ardra Krishna; Rose, Winnine; M, Gunasekaran (International Journal of Life Science and Pharma Research, 2022)
The design of the present investigation was to prepare Piroxicam bounded pharmacosomes to improve the water solubility, bioavailability and to minimize the gastrointestinal toxicity of Piroxicam. Pharmacosome is a potential approach in vesicular drug delivery systems which exhibits several advantages over conventional vesicular drug delivery systems. Pharmacosomes are phospholipid complexes with a potential to improve bioavailability of poorly water soluble as well as poorly lipophilic drugs. Piroxicam was complexed with soya phosphatidylcholine in various ratios using conventional solvent evaporation technique. In our study, Pharmacosomes thus prepared were subjected to drug solubility, drug content evaluation, surface morphology (by scanning electron microscopy), crystallinity (by X- ray powder diffraction), quality control tests for capsules and in-vitro dissolution study. Solubility profile of the prepared complexes was found to be much better than Piroxicam pure drug. This improvement in solubility of the prepared pharmacosomes may result in improved dissolution and lower gastrointestinal toxicity. Drug content was found to be 96.84%w /W for the optimized Piroxicam phospholipid complex, F1 (Piroxicam: lecithin ratio of 1:1). The pharmacosomes were found to be disc shaped in scanning electron microscopy. X-ray powder diffraction data confirmed the formation of phospholipid complexes. The formulation F1 showed 94.69% drug release while the free Piroxicam showed a total of only 60.42% at the end of 10-hour dissolution study. Thus the solubility and hence the bioavailability of Piroxicam can be increased to a greater extent by complexing it with soya phosphatidylcholine.